Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Higher Order Thinking Skill (HOTS) - Noprinda, Chintia Tri; Soleh, Sofyan M (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This study aims to produce a product of Student Worksheet (LKPD) Based on Higher Order Thinking Skill (HOTS) on the subject of static electricity and to know the feasibility of developing Student Worksheets (LKPD) Based on Higher Order Thinking Skill (HOTS) on Static Electricity Material developed. This study uses the Research and Development (R and D) method with a 4D (Four D Model) development model from Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel namely, Defining, Planning, Developing, and Spread (Disseminate). Validation is carried out by material experts and media experts by providing an assessment questionnaire to test the feasibility of the product. The trial was carried out through two stages, namely limited trials and field trials. The results of the material expert validation on the aspect of content eligibility obtained an average percentage of 82% with very good criteria. The feasibility aspect of presentation is obtained by an average percentage of 79% with very good criteria. The aspects of language feasibility obtained an average percentage of 78% with very good criteria, and HOTS assessment aspects obtained an average percentage of 81% with very good criteria. The validation of media experts on the aspect of the LKPD was obtained by an average percentage of 88% with very good criteria. The cover design aspects of the LKPD obtained an average percentage of 90% with excellent criteria and the design aspects of the LKPD contents obtained an average percentage of 93% with very good criteria. The results of the limited trial of class IX students obtained an average percentage of 85% with very good criteria and field trials of class IX students obtained an average percentage of 90% with very good criteria so that the LKPD was feasible and ready to be used as teaching material.  Abstrak: Penelitian ini bertujuan untuk menghasilkan produk Lembar Kerja Peserta Didik (LKPD) Berbasis Higher Order Thinking Skill (HOTS) pada pokok bahasan listrik statis  dan mengetahui kelayakan terhadap Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Higher Order Thinking Skill (HOTS) pada Materi Listrik Statis yang dikembangkan. Penelitian ini menggunakan metode Research and Development (R and D) dengan model pengembangan 4D (Four D Model) dari Thiagarajan, Dorothy S. Semmel, dan Melvyn I. Semmel yaitu, Pendefinisian (Define), Perencanaan (Design), Pengembangan (Develop), dan Penyebaran (Disseminate). Validasi dilakukan oleh ahli materi dan ahli media dengan cara memberikan angket penilaian untuk menguji kelayakan produk. Uji coba dilakukan melalui dua tahap yaitu uji coba terbatas dan uji coba lapangan. Hasil validasi ahli materi pada aspek kelayakan isi diperoleh rata-rata persentase sebesar 82% dengan kriteria sangat baik. Aspek kelayakan penyajian diperoleh rata-rata persentase sebesar 79% dengan kriteria sangat baik. Aspek kelayakan bahasa diperoleh rata-rata persentase sebesar 78% dengan kriteria sangat baik, dan aspek penilaian HOTS diperoleh rata-rata persentase sebesar 81% dengan kriteria sangat baik. Validasi ahli media pada aspek ukuran LKPD diperoleh rata-rata persentase sebesar 88% dengan kriteria sangat baik. Aspek desain cover LKPD diperoleh rata-rata persentase sebesar 90% dengan kriteria sangat baik dan aspek desain isi LKPD diperoleh rata-rata persentase sebesar 93% dengan kriteria sangat baik. Hasil uji coba terbatas peserta didik kelas IX memperoleh rata-rata persentase 85% dengan kriteria sangat baik dan uji coba lapangan peserta didik kelas IX memperoleh rata-rata persentase 90% dengan kriteria sangat baik sehingga LKPD layak dan siap digunakan sebagai bahan ajar.